Dissection of floral induction pathways using global expression analysis - Schmid, Markus; Lohmann, Jan U. (Development, 2003)
Flowering of the reference plant Arabidopsis thaliana is controlled by several signaling pathways, which converge on a small set of genes that function as pathway integrators. We have analyzed the genomic response to one type of floral inductive signal, photoperiod, to dissect the function of several genes transducing this stimulus, including CONSTANS, thought to be the major output of the photoperiod pathway. Comparing the effects of CONSTANS with those of FLOWERING LOCUS T, which integrates inputs from CONSTANS and other floral inductive pathways, we find that expression profiles of shoot apices from plants with mutations in either gene are very similar. In contrast, a mutation in LEAFY, which also acts downstream of CONSTANS, has much more limited effects. Another pathway integrator, SUPPRESSOR OF OVEREXPRESSION OF CO 1, is responsive to acute induction by photoperiod even in the presence of the floral repressor encoded by FLOWERING LOCUS C. We have discovered a large group of potential floral repressors that are down-regulated upon photoperiodic induction. These include two AP2 domain-encoding genes that can repress flowering. The two paralogous genes, SCHLAFMÜTZE and SCHNARCHZAPFEN, share a signature with partial complementarity to the miR172 microRNA, whose precursor we show to be induced upon flowering. These and related findings on SPL genes suggest that microRNAs play an important role in the regulation of flowering.